Analisis Saham di Pasar Modal Indonesia: Kinerja, Tantangan, dan Prospek Masa Depan - Nadjima, Aulia Rachmatullah; Andhiyo, Immanuel Given Bintang; Putra, Alfarel Endito (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Indonesian capital market has an important role in the country's economic activities, with its performance highly dependent on national, regional and international economic performance. This analysis provides a holistic picture of the performance of leading stocks, the dynamics of stock trading, and the driving factors in the capital market. This research explores what factors drive a significant increase in leading shares, including external factors such as changes in the global investment climate, national economic developments, and government policies that affect related sectors. Apart from that, internal aspects of the company such as financial performance, innovation and management strategy are also considered. Challenges faced by the Indonesian capital market include the limited types of securities traded, regulations for protecting investor rights,